Transcriptomic Dissection of Long-Juvenility in Soybean: A Comparative Study of Grobogan Cultivar and Its Derivative Long Juvenile AP18 Line - Rijzaani, Habib; Tasma, I Made (HAYATI Journal of Biosciences, 2026)
The long juvenile (LJ) trait in soybean extends the vegetative phase, enabling cultivation in low-latitude regions. This study investigated transcriptomic differences between the Grobogan cultivar (control) and the AP18 (LJ) soybean line using RNA-seq. Young leaf tissues from plants at the vegetative stage were collected under field conditions and sequenced using the Illumina NovaSeq 6000 platform. After quality filtering and alignment to the soybean reference genome, 24,716 expressed transcripts were retained for analysis. Differential expression analysis identified 5,005 upregulated and 4,534 downregulated transcripts in AP18 relative to Grobogan. Functional enrichment analysis revealed the upregulation of genes involved in ribosome biogenesis and secondary metabolism, and the downregulation of genes related to photosynthesis and energy metabolism. While known LJ-related genes FT2A (E9) and ELF3B (J) showed differential expression, the magnitude was modest. These findings highlight widespread transcriptomic reprogramming associated with the LJ trait, providing insight into potential pathways that influence juvenile phase extension.